253 KW Solar PV Power System Design for a Typical 500 Metric Ton Capacity Above Zero Cold Storage in Farah Province - Aslami, Alyas; Yousufzai, Mumtaz Ahmad; Stanikzai, Hasibullah; Sharifi, Mohammad Shahab (PT. Riset Press International, 2024)
This study carries out design of 253 KW PV system for a 500 metric ton cold storage in Farah province. The design includes estimation and calculation of number of solar panel, inverter, batteries, and required land. Farah province located in western part of Afghanistan that has huge solar potential and 300 sunny days. The design of this PV system has calculated carefully. The methodology of this study includes descriptive analysis and formulas. For design o 253 KW PV system is necessary 421 modules, 8 inverters with 326.8 KW, 868 batteries, and 1234 m2 area or land. This will have positive impact on climate change and weather. The design of 253 KW PV system has need to more and careful consideration of different factors such as orientation, capacity of inverter and batteries, number of panels, batteries, and inverter.